Transformasi Digital Kantor Urusan Agama di Kabupaten Buton Tengah: Evaluasi Infrastruktur dan Kebijakan - Asa, La Indo (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper examines the digitalization of public services as a strategic step in increasing efficiency and transparency. However, its implementation at the Office of Religious Affairs (KUA) of Central Buton Regency still faces various obstacles. The main problem identified is the limited technology infrastructure caused by several main factors, including unstable internet access and frequent disruptions that hamper the operation of applications, such as the Marriage Management Information System (SIMKAH), so that the process of marriage services operates a digital system. The main objective of this policy paper is to analyze the inhibiting factors for the digitalization of KUA and to formulate policies that can optimize the implementation of technology-based services. This paper uses a qualitative method with a descriptive-analytical approach to data collected from: literature studies, in-depth interviews, surveys, and policy analysis using the SWOT approach and evaluation of alternative policies based on the criteria of effectiveness, efficiency, and sustainability. The analysis results show that the lack of an internet network, limited technological devices, and lack of employee training hamper the efficiency of administrative services at KUA. Based on the evaluation of alternative policies, the issuance of the Minister of Religion Regulation (PMA) on technology infrastructure standards and digitalization of KUA services was chosen as the most effective solution to accelerate digital transformation. Based on the results of the analysis, it is recommended that the Indonesian Ministry of Religion immediately issue a PMA to ensure the optimal sustainability of the digitalization of KUA services.